Thermoelectric properties of phosphorus-doped indium tellurosilicate: InSiTe3 - Tawat Suriwong (2018)
© 2017 Elsevier B.V. Polycrystalline samples of undoped and doped indium tellurosilicate: InSiTe3were synthesized and their thermoelectric (TE) properties were investigated in the temperature range from 323 to 723 K. Phosphorus (P) was selected as an electron dopant, i.e., the starting compositions were set as InSi1-xPxTe3(x = 0, 0.02, 0.04, 0.06, and 0.1), The P doping increases the carrier concentration, which leads to decrease in both the electrical resistivity (ρ) and the Seebeck coefficient (S), while has little effect on the thermal conductivity (κ). As the results, the figure of merit ZT = S2ρ−1κ−1T increases with increasing the P content. The maximum ZT value is 0.14 at 723 K, obtained for InSi0.9P0.1Te3. The present results suggest that InSiTe3can be a good TE material.